(untitled) (International journal of artificial intelligence, 2025)
This article investigates the specific features of speech style as a key component of linguistic, communicative, and socio-cultural competence. Using IMRAD structure, the study analyzes how phonetic, lexical, syntactic, and pragmatic choices shape functional styles such as conversational, scientific, official-business, publicistic, and artistic styles. Drawing on Uzbek scholarly sources, the research demonstrates that speech style is determined not only by linguistic norms but also by communicative intentions, social relationships, and cultural expectations of speakers. The findings reveal that speech style is a dynamic phenomenon that adapts to changing communication needs in contemporary society.